The identification of organisational subcultures in an international energy company : a 219.899 thesis presented in partial fulfilment of the requirements of the degree of Master of Management at Massey University, Auckland, New Zealand - Reynolds, Carol Anne (Massey University, 2010)
For more than half a century it has been hypothesised that organisational culture is a single, homogeneous and consistent phenomenon, which provides an overarching set of meanings shared by all organisational members. Increasingly, however, the efficacy of this approach has been tested as a small number of scholars have put forward an alternative hypothesis – that, like the societies they are part of, organisations are more likely characterised by pluralism, heterogeneity and ambiguity. The possibility of subcultures as the dominant expression of organisational culture has gained support as a means to understand and explain the cultural milieu of the highly complex organisations of the 21st century. This research, an embedded single case study, examines the procurement directorate (PD) of a large, multinational energy company, to identify whether subcultures exist in this context, and if so, whether they can be defined using current theoretical concepts. Content analysis of the data shows that a number of unique subcultural groups do exist, which are delineated by a variety of unifying characteristics and physical manifestations of the group’s culture. These distinct subcultures emerge as being influential in a variety of different ways: at the operating unit level through sustaining harmonious relationships with one another and supporting the day-to-day work of the directorate; and at the organisational level through fostering positive relationships between group members and ZAOC Norge and the overt support of important organisational meanings. The findings from this study suggest that subcultures are central to the cultural environment of the PD and moreover contribute to the maintenance of the strong overarching organisational culture that exists at ZAOC Norge. However, with the lack of generalisability from a single case study, more research is required in both other procurement directorates and also alternative directorates of the petroleum industry. Further research would help to address the paucity of studies that exist within the industry and the lack of subcultural knowledge in this context
Keywords: Organisational subcultures; Heterogeneity; Organisational culture; Petroleum industry; International companies